Optoelectronic forces with quantum wells for cavity optomechanics in GaAs/AlAs semiconductor microcavities - Villafañe, Viviana Daniela (2018)
Radiation pressure, electrostriction, and photothermal forces have been investigated to evidence backaction, nonlinearities, and quantum phenomena in cavity optomechanics. We show here through a detailed study of the relative intensity of the cavity mechanical modes observed when exciting with pulsed lasers close to the GaAs optical gap that optoelectronic forces involving real carrier excitation and deformation potential interaction are the strongest mechanism of light-to-sound transduction in semiconductor GaAs/AlAs distributed Bragg reflector optomechanical resonators. We demonstrate that the ultrafast spatial redistribution of the photoexcited carriers in microcavities with massive GaAs spacers leads to an enhanced coupling to the fundamental 20-GHz vertically polarized mechanical breathing mode. The carrier diffusion along the growth axis of the device can be enhanced by increasing the laser power, or limited by embedding GaAs quantum wells in the cavity spacer, a strategy used here to prove and engineer the optoelectronic forces in phonon generation with real carriers. The wavelength dependence of the observed phenomena provide further proof of the role of optoelectronic forces. The optical forces associated with the different intervening mechanisms and their relevance for dynamical backaction in optomechanics are evaluated using finite-element methods. The results presented open the path to the study of hitherto seldom investigated dynamical backaction in optomechanical solid-state resonators in the presence of optoelectronic forces.